Development, Implementation, and Compliance of Treatment Pathways in Radiation Medicine - Potters, Louis (Frontiers in Oncology, 2013)
INTRODUCTION: While much emphasis on safety in the radiation oncology clinic is placed on process, there remains considerable opportunity to increase safety, enhance outcomes and avoid ad-hoc care by instituting detailed treatment pathways. The purpose of this study was to review the process of developing evidence and consensus-based, outcomes-oriented treatment pathways that standardize treatment and patient management in a large multicenter radiation oncology practice. Further, we reviewed our compliance in incorporating these directives into our day-to-day clinical practice. METHODS: Using the Institute of Medicine guideline for developing treatment pathways, 87 disease specific pathways were developed and incorporated into the electronic medical system in our multi-facility radiation oncology department. Compliance in incorporating treatment pathways was assessed by mining our EMR data from January 1, 2010 through February 2012 for patients with breast and prostate cancer. RESULTS: This retrospective analysis of data from electronic medical records found overall compliance to breast and prostate cancer treatment pathways to be 97% and 99%, respectively. The reason for non-compliance proved to be either a failure to complete the prescribed care based on grade II or III toxicity (n=1 breast, 3 prostate) or patient elected discontinuance of care (n=1 prostate) or the physician chose a higher dose for positive/close margins (n=3 breast). CONCLUSION: This study demonstrates that consensus and evidence-based treatment pathways can be developed and implemented in a multi-center department of radiation oncology. And that for prostate and breast cancer there was a high degree of compliance using these directives. The development and implementation of these pathways serve as a key component of our safety program, most notably in our effort to facilitate consistent decision-making and reducing variation between physicians.